Functional outcome predictors and recanalization in cerebral venous thrombosis: A single-center cross-sectional study - Rizwana Shahid; Azra Zafar (Turkish Journal of Emergency Medicine)
OBJECTIVES Cerebral venous thrombosis (CVT) is a rare type of stroke. Functional outcome (FOC) in CVT can be affected by different factors, and recanalization is an important determinant. This study aimed to identify the FOC predictors including recanalization in patients with CVT. METHODS This retrospective study reviewed electronic charts of patients with CVT admitted to the King Fahd Hospital of the University, a teaching and referral hospital between January 2012 and March 2023. Demographic and other clinicoradiological characteristics were noted. Factors affecting FOC were investigated using the Chi-square test, odds ratios (ORs), and 95% confidence interval (CI). RESULTS Out of 64 patients, 78% achieved good FOC. Age was significantly higher in patients having poor FOC as compared to those having good FOC (P ≤ 0.001). Women had more likelihood to be functionally independent as compared to men (OR = 1.35, 95% CI = 1.01–1.80, P = 0.02). Altered consciousness (OR = 2.94, 95% CI = 1.23–6.99, P = 0.01), venous hemorrhagic infarction (OR = 3.26, 95% CI = 1.36–7.82, P = 0.008), and nonrecanalization (OR = 1.44, 95% CI = 0.97–2.14, P = 0.02) were significantly associated with poor FOC. Hereditary thrombophilia (OR = 0.60, 95% CI = 0.31–1.12, P = 0.03) and infections (OR = 0.59, 95% CI = 0.31–1.12, P = 0.01) were associated with less likelihood of good FOC. Age ≥50 years (P = 0.01) and illness of more than 1-month duration (P = 0.01) were associated with nonrecanalization. CONCLUSION Older age, male sex, presence of venous hemorrhagic infarction, and nonrecanalization can predict poor FOC in CVT. The recanalization process can be affected by late presentation, and the plausible reason could be a delay in therapeutic anticoagulation. Further prospective and multicenter studies are needed to determine the predictors of FOC and to understand the process of recanalization in CVT.